Interaksi Guru Pendidikan Agama Islam dan Peserta Didik dalam Membentuk Kepribadian Muslim di Sekolah Menengah Kejuruan (SMK) Negeri 1 pacitan - , Sugiharto, Dr. Sudarno Shobron, M.Ag, Dr. Badaruddin, M.Ag (2014)
Islamic religious education is a conscious effort of teaching, guidance and training to students that will be able to understand, appreciate and practice the values and teachings of Islam as a way to make everyday life that Muslim personality. It all depends on bridging institutions ( mediator ) of the students in learning. Islamic religious education teacher is one who took a lot of contributing and responsible in guiding and directing students in shaping his personality. Therefore, the authors tried to explore a study to uncover how the interaction of Islamic religious education teachers and learners in order to establish a Muslim personality in SMK 1 Pacitan, barriers to interaction of Islamic religious education teachers and learners in order to establish a Muslim personality in SMK 1 Pacitan and how efforts made to overcome barriers PAI Teacher interaction and learners in order to form a Muslim personality in SMK 1 Pacitan. The purpose of this study is to investigate the interaction of Islamic religious education teachers and learners in SMKN1 Pacitan in shaping the personality of a Muslim, to know Constraint Interaction Islamic Education Teachers and students at SMK 1 Pacitan in shaping the personality of a Muslim . To determine the interaction Addressing Barriers to Teacher PAI and learners at SMK 1 Pacitan . This study used a qualitative approach . In an effort to get the data source, the author uses the method of observation, interviews, and documentation. While the researchers used data analysis technique descriptive qualitative analysis, the form of data written or oral from Master PAI principals , and children at SMK 1Pacitan.yang has been observed that in this case the authors attempt to describe the whole of the real situation . Results of research conducted , submitted that the interaction of PAI Teachers and learners in shaping the personality mulim at SMK 1 Pacitan through PAI Teacher approaches with students either through an individual approach , and educational groups , students look at the run time of worship , followed in school activities such as extracurricular activities , the anniversary of the birthday of the prophet of Islam great , the attitude of students towards teachers and friends , and also when Guru PAI carrying out the process of learning , the teacher with a sincere attitude , and do , and try to understand their students with all konsekuensinya.sehingga formed harmonious relationship between the two and can practice the moral values of Islam that Muslim personality . Factors that inhibit the interaction of teachers and students preformance PAI forming Muslim personalities internal factors and external factors . Internal factors related to the lack of time for lessons , school policies that provide double duty on PAI Teachers , school facilities and infrastructure are inadequate. The external factors include the lack of knowledge and religious instruction received by the students of parents and previous education , lack of parental indifference and the public on the importance of Islamic religious instruction , a variety of activities that support the development of time and immoral activities , as well as families who are less Islamic . From this research, the researcher can conclude that the presence of PAI teacher interaction and students in shaping the personality of the Muslims will be in the running PAI conducive learning process . And is also expected to establish personal Pirbadi students to become true Muslims.